SISTEM MONITORING PENJUALAN BAHAN BANGUNAN MENGGUNAKAN PENDEKATAN KEY PERFOMANCE INDICATOR - Muhtad Fadly; Dina Ros Muryana; Adhie Thyo Priandika (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2020)
PT Indojava Kreasindo is one of the distributors of Kramik sanitari granite, which has a role in distributing these goods throughout the city of Lampung and its surroundings. The management of ceramic and granite sales data has been summarized in the sales recap sheet for each sales each month in writing so it takes a long time to find out the achievements of each sales each month. Therefore, the authors propose the application of sales monitoring to make it easier to find out the achievements of each sales per month. To solve this problem, we need the most effective solution, which is the Development of Monitoring Application for Building Materials Sales Using the Key Performance Indicator (KPI) Approach. In the development of this application using the waterfal method. For the data flow method using the Usacase Diagram, Activity Diagram. The concept used is monitoring using the KPI approach to facilitate the general manager in monitoring the sales of each sales. With the construction of a web-based information system and sales monitoring application aims to make it easier for the general manager to monitor the sales of each sales so that it does not require a long time and is presented in the form of a dashboard.